KEINOVATIVAN GURU DALAM MENGEMBANGKAN MUTU SEKOLAH PADA MADRASAH - Rita Sahara Munte; Mukhtar; Kasful Anwar; Mahmud MY (LPPM Universitas Cipta Mandiri, 2024)
This article discusses in depth the innovation of teachers in madrasa schools today. Teachers are at the forefront of improving the quality of education and creating competitive and characterful human resources. Teacher innovation, when applied well, can be the main driver in developing Madrasah Schools into educational centers that are quality, relevant and responsive to student needs and the demands of modern society. The main focus is to identify innovative strategies, methods and approaches used by teachers to improve the quality of education and enrich students' learning experiences. Research methods are used to gain in-depth insight into document analysis. The research results show that madrasa teachers are not only information providers, but also innovators who actively create a stimulative learning environment. Teacher innovation is manifested in creative learning design, use of technology, and empowering students to think critically. These findings contribute to our understanding of the role of teachers as agents of change in the madrasa context, while also providing a foundation for the development of more effective Islamic education policies.